Chronic toxicity of triphenylarsine to Danio rerio - Wojciech Wilczynski; Tomasz Brzeziński; Jakub Nawała; Daniel Dziedzic; Stanisław Popiel; Marcin Lukasz Zebrowski; Michał Czub; Jacek Bełdowski; Monika Radlinska (Ecotoxicology and Environmental Safety)
Triphenylarsine (TPA) is a persistent organoarsenical that has emerged as a major environmental concern due to the extensive marine disposal of chemical munitions throughout the 20th century. The waterborne toxicity of TPA in aquatic organisms remains poorly understood, with limited and often inconclusive data, and its chronic effects are entirely unexplored. To address this gap, a 28-day exposure study was conducted, focusing on assessing the long-term toxicity of TPA in the model fish species Danio rerio. The results indicate that chronic exposure to trace concentrations of TPA significantly reduces body length, weight, and growth rate in fish. Furthermore, TPA and its primary degradation product, triphenylarsine oxide (TPAO), accumulate in the muscle tissues of fish. The accumulation rates are 0.61 μg × g⁻¹ (dry weight) for TPA and 9.1 μg × g⁻¹ (dry weight) for TPAO, for every microgram of TPA per litre of water over 28 days of exposure. Additionally, chronic exposure induced oxidative stress in the gills, as evidenced by altered mRNA expression and elevated enzymatic activity of detoxification-related proteins. Therefore, TPA exposure represents a significant threat to fish. This compound should be recognized as a high-priority environmental contaminant, and its concentrations should be routinely monitored in bottom waters, particularly near chemical munitions dumping sites. Expanding research to predict and assess the toxicity of other persistent organoarsenicals co-disposed with TPA is essential for understanding their cumulative ecological and health impacts.